Explorando a síntese de ítrio-alumínio-granada - YAG: uma cerâmica transparente - Cruz, Igor Barbosa (Universidade Federal de São Carlos, 2023)
Yttrium aluminum garnet (YAG) is a transparent ceramic with a cubic crystalline structure that has highly relevant technological applications. When doped, it is used as a solid-state laser and X-ray scintillator. In this work, our aim is to produce and apply it as an X-ray sensor in Sirius. Its synthesis is carried out using the coprecipitation method, involving solutions of aluminum nitrate (III) and yttrium nitrate (III) in a basic medium of ammonium bicarbonate in deionized water (pH ~ 8). This process yields a precursor that will be calcined in a furnace at temperatures between 900 1100 °C for one hour, promoting a solid-state reaction to form YAG. The obtained samples were analyzed by X-ray diffraction (XRD), when the precursor was calcined at 900 °C, the data demonstrated a phase mixture (YAlO3 - YAP and Y3Al5O12 - YAG), which did not occur when the temperature of 1100 °C was used. Microscopy analysis provided information about particle size and morphology, revealing particles with an average size of approximately 43 nm and necked like structures at a temperature of 1100 °C. However, upon analyzing the XRD data of the produced pellet and indexing the peaks, the presence of α-Al2O3 (corundum alumina) as a secondary phase was observed. Further investigation using scanning electron microscopy (SEM) allowed for the identification of this secondary phase, which was subsequently confirmed by transmission electron microscopy (TEM) analysis of the calcined powder, showing the presence of alumina on the powder surface. The next steps involve studying the synthesis parameters to achieve the production of pure YAG powder, followed by the intention to dope it with Cerium for use as an X-ray scintillator in Sirius.
Exploring the synthesis of yttrium-aluminum-garnet - YAG: a transparent ceramic
Keywords: YAG; Coprecipitação; Sinterização; Cintilador; Coprecipitation; Sintering; Scintillator; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA